Distribution characteristics of endemic and rare plants along the altitudinal gradient in Bat Xat nature reserve in Vietnam - Quang, Bui Hong; Binh, Tran Duc; Van Hai, Do; Han, Le Ngoc; Hoan, Duong Thi; Huong, Nguyen Thi Thanh; Thuong, Vu Anh; Hiep, Trinh Ngoc (Academia Journal of Biology, 2021)
This study aimed to assess the relationship between distribution, altitude and investigation lines of vascular plants in Bat Xat Nature Reserve, Lao Cai province. Based on the collected specimens added 273 species of vascular plants belonging to 48 genera, 18 families, bringing the total number the currently known species are 1245 species of vascular plants belonging to 649 genera, 174 families and under 6 divisions such as. Of these, and there are 211 endemic and rare species consists have been recorded and 22 rare species 17 endemic species and updated scientific name 14 species added checklist to the Nature Reserve. Topographic, vegetation and distribution maps, changes in diversity and a checklist of endemic and rare species are shown.